Great recession and the informational shifts: new evidence from sticky information Phillips curve. Issue 1 (2nd January 2020) - Kumar, Saten
ABSTRACT: We utilize the nonlinear least squares (NLLS) and seemingly unrelated regression (SUR) techniques to estimate information stickiness parameter λ for the USA. We find that λ values appeared in a somewhat humped shape or inverted U pattern during the financial crisis. Prior to the financial crisis (1978.Q1-2006.Q4), λ was around 0.3. However, when the sample is extended to include the financial crisis period (1978.Q1-2011.Q4), λ increased to around 0.6. Results imply that during the financial crisis many firms became flexible and efficient and used updated information to set optimal prices.